2016
DOI: 10.1016/j.bbrc.2016.09.131
|View full text |Cite
|
Sign up to set email alerts
|

The SH3 domain distinguishes the role of I-BAR proteins IRTKS and MIM in chemotactic response to serum

Abstract: The family of inverse BAR (I-BAR) domain proteins participates in a range of cellular processes associated with membrane dynamics and consists of five distinct members. Three of the I-BAR proteins, including insulin receptor tyrosine kinase substrate (IRTKS), contain an SH3 domain near their C-termini. Yet, the function of the SH3 domain of IRTKS remains uncharacterized. Here we report that in contrast to MIM, which is a prototype of I-BAR proteins and does not contain an SH3 domain, IRTKS promoted serum-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The I-BAR domain is a common structure of I-BAR superfamily members, and can induce plasma membrane protrusion formation [12]. The SH3 domain, known as a protein recognition module, could serve as a docking harbor [13]. Here, we found that the SH3 domain mediates the binding of IRTKS to SHIP2.…”
Section: Discussionmentioning
confidence: 83%
“…The I-BAR domain is a common structure of I-BAR superfamily members, and can induce plasma membrane protrusion formation [12]. The SH3 domain, known as a protein recognition module, could serve as a docking harbor [13]. Here, we found that the SH3 domain mediates the binding of IRTKS to SHIP2.…”
Section: Discussionmentioning
confidence: 83%
“…We were interested in whether interaction with RABs is a common property of I-BAR domain proteins and thus analyzed HeLa cells expressing GFP-conjugated IRTKS (IRTKS-GFP). We chose IRTKS because we had found previously that it regulates cellular motility differently than MIM does (29) and that it is structurally distinct from MIM by having an internal SH3 domain ( Fig. 4A).…”
Section: Mim and Irtks Bind To Different Rabs And Regulate Cxcr4 Intementioning
confidence: 99%
“…PBS was from Corning. The plasmids encoding MIM-GFP, IRTKS-GFP, IRTKS⌬SH3-GFP, IRTKS-IBAR-MIM-GFP, and MIM-IBAR-IRTKS-GFP have been described previously (29).…”
Section: Antibodies Chemicals and Plasmidsmentioning
confidence: 99%
“…The MTSS1 (Missing in Metastasis 1) protein is considered the prototype of I-BAR proteins (Li et al, 2016), but, to the best of our knowledge, has not previously been applied in an optogenetic context. In this work, we investigated the potential of the MTSS1 I-BAR domain to serve as an actuator of membrane architecture and plasma membrane dynamics.…”
Section: Introductionmentioning
confidence: 99%